Effect of Supplementing Moringa Forage Meal and Boron on Sperm Production and Quality in Breeding Jersey Bulls - Binsila, Balakrishnan; Selvaraju, Sellappan; Gowda, Shivakumar; Krishnappa, Balaganur; Kumar Dey, Debpriyo; Athira, Thomas; Taran Pal, Din; Sahoo, Artabandhu; Bhatta, Raghavendra (The Indian Journal of Animal Reproduction, 2026)
The testicular microenvironment influences semen production capacity and consequently the reproductive potential of the male. In the present study, Moringa oleifera (moringa) and boron were supplemented in Jersey bulls to assess total sperm output and quality. In a completely randomised design, 28 healthy Jersey bulls were selected and supplemented with moringa and boron (sodium borate) for sixty days. These animals were divided into four groups (n=7 each), group-1 (control), group-2 (70g moringa forage meal/day), group-3 (40ppm boron as sodium borate) and group-4 (40ppm boron plus 70g moringa forage meal/day). Before the start and at the end of the feeding experiment, semen samples were eval uated for sperm functional attributes and semen production capacity of the bulls. A significant (p
Keywords: Moringa oleifera; boron; sperm production; Jersey bulls